1997
DOI: 10.1111/j.1360-0443.1997.tb02913.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of law enforcement activity on a heroin market

Abstract: It may be argued that seizing large quantities of heroin being imported into the country should decrease its supply and hence increase its price, resulting in a reduction in the quantity of the drug being purchased or consumed. To date, however, there has been no empirical evidence that heroin seizures in Australia have any effect on the price of heroin at street level. This article describes a 2-year research study during which the price and purity of street-level heroin were regularly monitored. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 15 publications
1
34
3
Order By: Relevance
“…All but two of the studies reported cover cocaine; heroin is the exclusive focus of Weatherburn & Lind [35], and is included along with cocaine in Yuan & Caulkins [34]. The time-periods covered stretch from the early 1980s to approximately 2010.…”
Section: Interpreting the Evidencementioning
confidence: 99%
“…All but two of the studies reported cover cocaine; heroin is the exclusive focus of Weatherburn & Lind [35], and is included along with cocaine in Yuan & Caulkins [34]. The time-periods covered stretch from the early 1980s to approximately 2010.…”
Section: Interpreting the Evidencementioning
confidence: 99%
“…A recent systematic review revealed the effects of denial of harm reduction services, law enforcement practices, and discriminatory access to ART on vulnerability to HIV and service access (Jurgens et al, 2010). For instance, police presence and harassment in the vicinity of needle exchange programs have been found to lead to decreased attendance at voluntary treatment programmes and needle exchange sites, increased needle sharing, unsafe injecting and improper disposal of needles (Rhodes et al, 2005; Rhodes et al, 2003; Aitken et al, 2002; Blankenship & Koester, 2002); Best et al, 2001; Maher and Dixon, 1999; Weatherburn and Lind, 1997; Bluthenthal et al, 1999). These factors have been found to increase the likelihood of IDUs in acquiring HIV infection (Broadhead et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This situation violates the right against arbitrary arrest as granted in Article 9 of the Universal Declaration of Human Rights (UDHR) and the ICCPR (United Nations High Commissioner for Refugees, 1976), to which India is a signatory. Studies in other regions of the world indicate that intense enforcement drives IDUs underground (Aitken et al, 2002;Bastos & Strathdee, 2000;Best et al, 2001;Bluthenthal et al, 1999;Darke et al, 2002;Davis, Burris, Kraut-Becher, Lynch, & Metzger, 2005;Maher & Dixon, 1999;Rhodes et al, 2003;Rhodes, Singer, Bourgois, Friedman, & Strathdee, 2005;Weatherburn & Lind, 1997). Low utilization of services as a result of being arrested by the police for carrying needles has been echoed in several previous studies (Aitken et al, 2002;Callon et al, 2006;Grund, Stern, Kaplan, Adriaans, & Drucker, 1992;Maher & Dixon, 1999;Wood et al, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…Much of this success can be attributed to the ability of these programs to function without governmental restrictions or police intervention. Evidence shows that police activities indeed result in decreased uptake of voluntary drug user treatment and needle exchange services, increases in needle sharing, unsafe injecting, and improper disposal of needles (Aitken, Higgs, Kersall, & Kerger, 2002;Best, Beswick, & Gossop, 2001;Bluthenthal, Kral, Erringer, & Edlin, 1999;Darke, Topp, Kaye, & Hall, 2002;Maher & Dixon, 1999;Rhodes et al, 2003;Weatherburn & Lind, 1997). While most of this evidence comes from higher-income country settings, there is not much known about the impact of harsh drug control measures on the use of services in lower-and middle-income settings with injection-driven HIV epidemics.…”
Section: Since the Advent Of The World Health Organization's (Who's) mentioning
confidence: 89%